Visionary evaluation for a sustainable, equitable future - Parsons, Beverly A.; Dhillon, Lovely; Keene, Matt (Evaluation and society., 2020)
"Take a journey to 2030 where Visionary Evaluatives abound and link with one another in actively bringing about a sustainable, equitable future. Utilizing a creative storytelling approach, Visionary Evaluation for a Sustainable, Equitable Future brings forward the centrality of values in conjunction with the role of evaluation in building a future of well-being for people, nature, and planet. Visionary Evaluatives are guided by six principles. Those principles highlight a commitment to equity and the sustainability of nature as core values. They emphasize an orientation of humility, compassion, and transparency as Visionary Evaluatives engage with others in a world of living, entangled systems with both obvious and hidden intersectionalities. They require Visionary Evaluatives to engage in deep praxis-mindful and challenging reflection on what is being learned through the intersection of values, iterative action and inquiry, theory, outcomes, and vision. A diverse group of chapter authors share their wisdom through envisioning 2030 and what it might mean to move in the world applying aspects of the Visionary Evaluative Principles. Through Visionary Evaluation for a Sustainable, Equitable Future, you will learn about how you can contribute to a sustainable, equitable future not only in evaluations, as either users or practitioners, but also in your daily actions and lives"--